Minutes - First Meeting of the Food and Essential Services Committee, 1 May 1926
1926-05-01 "Minutes - First Meeting of the Food and Essential Services Committee, 1 May 1926" [g0566001.jpg], 1 May 1926, Trades Union Congress TUC Organisation